Interleukin-27 is a potent inhibitor of cis HIV-1 replication in monocyte-derived dendritic cells via a type I interferon-independent pathway. - Qian Chen; Sanjay Swaminathan; De Yang; Lue Dai; Hongyan Sui; Jun Yang; Ronald L Hornung; Yanmei Wang; Da Wei Huang; Xiaojun Hu; Richard A Lempicki; Tomozumi Imamichi (PLoS ONE)
IL-27, a member of the IL-12 family of cytokines, plays an important and diverse role in the function of the immune system. Whilst generally recognized as an anti-inflammatory cytokine, in addition IL-27 has been found to have broad anti-viral effects. Recently, IL-27 has been shown to be a potent inhibitor of HIV-1 infection in CD4+ T cells and macrophages. The main objective of this study was to see whether IL-27 has a similar inhibitory effect on HIV-1 replication in dendritic cells (DCs). Monocytes were differentiated into immature DCs (iDCs) and mature DCs (mDCs) with standard techniques using a combination of GM-CSF, IL-4 and LPS. Following differentiation, iDCs were infected with HIV-1 and co-cultured in the presence or absence of IL-27. IL-27 treated DCs were shown to be highly potent inhibitors of cis HIV-1, particularly of CCR5 tropic strains. Of note, other IL-12 family members (IL-12, IL-23 and IL-35) had no effect on HIV-1 replication. Microarray studies of IL-27 treated DCs showed no up-regulation of Type I (IFN) gene expression. Neutralization of the Type-I IFN receptor had no impact on the HIV inhibition. Lastly, IL-27 mediated inhibition was shown to act post-viral entry and prior to completion of reverse transcription. These results show for the first time that IL-27 is a potent inhibitor of cis HIV-1 infection in DCs by a Type I IFN independent mechanism. IL-27 has previously been reported to inhibit HIV-1 replication in CD4+ T cells and macrophages, thus taken together, this cytokine is a potent anti-HIV agent against all major cell types targeted by the HIV-1 virus and may have a therapeutic role in the future.